Dari Petani Tradisional menjadi Koeli Perkebunan: Perubahan Mata Pencaharian Masyarakat Deli (1863-1869) - Hanif Harahap; Dimas Ade Gunawan; Sri Karina (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This article aims to describe the social changes of the Deli community livelihood as traditional farmers to become koeli (coolies) during 1863-1869. This is historical research with four steps includes heuristics, criticism (internal and external), interpretation, and historiography. Historical source collected by library research includes the primary and secondary sources. Based on the research results, before the opening of the tobacco plantations, Deli was still dominated by ancient forests, the people of Deli mostly relied on the fertility of the Deli soil to fulfill their daily needs by becoming traditional farmers. In 1863, Deli began to be used as a plantation area by the Dutch which was pioneered by Jacobus Nienhuys, the people and traditional farmers in Deli began to become coolies with daily wages.